KAJIAN KESESUAIAN WISATA PANTAI DAN DAYA DUKUNG PANTAI RUTAH, KECAMATAN AMAHAI, KABUPATEN MALUKU TENGAH - Lilis Tiawati; Henderina Lelloltery; Billy Seipalla (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study has two main objectives, namely (1) Analyzing the level of suitability of the tourist area at Rutah Beach located in Amahai District, Central Maluku Regency and (2) Assessing the physical capacity of the Rutah Beach area. In collecting visitor data, the researcher applied the Accidental sampling technique. Based on the analysis conducted, the Rutah Beach recreation area located in Rutah Village, Amahai District, Central Maluku Regency obtained an average Tourism Suitability Index (IKW) score of 85%, which places it in the